Detection the Ability of Escherichia Coli to Produce Biofilm and their Resistance to Some Antibiotics - Esraa Ahmed Abbas; Ali Jaffar Saleem (Scholars Digest Publishing, 2023)
In current study, 150 samples were collected from patients with urinary tract infection of both genders and all ages from October 2021 to January 2022 in Diyala and Baghdad governorates , Iraq . They were tested by phenotypic methods and the results showed that 73 isolates belonged to E.coli.
Keywords: E.coli, Biofilm , Antibiotics, MDR,UTI